Borum Eshøj Revisited: Bronze Age monumental burial traditions in eastern Jutland, Denmark - Frost, Lise; Løvschal, Mette; Lindegaard, Marianne Rasmussen; Holst, Mads Kähler (Danish Journal of Archaeology, 2017)
Borum Eshøj is one of the internationally most famous monuments from the Nordic Bronze Age, key to understanding burial customs, social identities and societies. Its uniqueness is reflected in its extraordinarily well-preserved oak log coffin burials, its landscape setting in a distinct barrow group and its complex monumental architecture. Since 1988, new investigations have been conducted at the barrow group, and in 2011, the remains of the classic Borum Eshøj were investigated. The new investigation reveals a monument with an extraordinarily long and complex use-life. It demonstrates a consecutive construction procedure with basic building principles which provide a basis for reinterpreting the barrow and suggesting an initial burial ground compounded beneath one large barrow construction phase. The kerbstones were constructed before the barrow was finished, and the barrow partly covers the kerbstone construction. In a larger perspective, the new investigations indicate that Borum Eshøj, with its construction, use history and kerbstones, stands apart from the investigated local barrows on the Eshøj plateau, and closer parallels barrows situated at much larger distance such as Hohøj in Mariager Fjord.